2014
DOI: 10.1177/1745691614521243
|View full text |Cite
|
Sign up to set email alerts
|

Missed Programs (You Can’t TiVo This One): Why Psychologists Should Study Media

Abstract: Media psychology involves the scientific examination of the cognitive processes and behavior involved in the selection, use, interpretation, and effects of communication across a variety of media (e.g., via the Internet, television, telephone, film). Media are central to people's lives, with projections indicating that an average person spent over 3,515 hours using media in 2012. New technologies are increasing the importance of media. Data from two content analyses demonstrate the underrepresentation of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 95 publications
2
36
0
Order By: Relevance
“…Thus, the children and parents seem to acquire knowledge of the new skills through the internet component, and the face-to-face sessions may permit the children and parents to perform and practice skills they have learned, and to apply them to their particular circumstances. This integration of the two formats in the intervention is consistent with the cross-channel additivity hypothesis (Okdie et al, 2014) which presumes that the overall intervention could be strengthened by taking advantage of the unique properties of each media channel (in the current case, internet and face-to-face interaction). The use of multiple channels in intervention delivery uses the internet and the narrative stories in the cartoon series on the webpages to increase children’s and parents’ participation in the program and their retention of material (Kennedy, 2004), while retaining the face-to-face time with the clinician.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, the children and parents seem to acquire knowledge of the new skills through the internet component, and the face-to-face sessions may permit the children and parents to perform and practice skills they have learned, and to apply them to their particular circumstances. This integration of the two formats in the intervention is consistent with the cross-channel additivity hypothesis (Okdie et al, 2014) which presumes that the overall intervention could be strengthened by taking advantage of the unique properties of each media channel (in the current case, internet and face-to-face interaction). The use of multiple channels in intervention delivery uses the internet and the narrative stories in the cartoon series on the webpages to increase children’s and parents’ participation in the program and their retention of material (Kennedy, 2004), while retaining the face-to-face time with the clinician.…”
Section: Discussionsupporting
confidence: 80%
“…Parent attendance in parent groups has been found to be related to the strength of children’s outcomes in dosage analyses (Lochman et al, 2006) in some studies, but not related to outcomes in other studies (Nix, Bierman, McMahon, & Conduct Problems Prevention Research Group, 2009). A set of recent studies have begun to examine predictors of parent attendance in parent behavioral training groups, and, for example, have found poorer attendance by parents who had experienced more stressful life events and who had more limited adult social supports (Minney, Lochman, & Guadagno, 2014). Thus some parents, including those most in need, may be at particular risk for low attendance in parent groups.…”
Section: Coping Power Programmentioning
confidence: 99%
“…90 Mothers are highly engaged with the Internet and social media and use the these tools to seek information about parenting and child health. [91][92][93][94] Mothers have also expressed interest in joining online communities focused on child health. 95 In 2014, women were more likely than men to use Facebook (77% vs. 66%), Pinterest (42% vs. 13%), and Instagram (29% vs. 22%).…”
Section: Social Media Is An Emerging Context For Social Influence Pamentioning
confidence: 99%
“…As of this writing, Developmental Psychology has published one article on text messaging and two on social media, in addition to a 2006 special section (Greenfield & Yan, 2006) and a 2012 special section focused broadly on Interactive Media (including video games, interactions with robots, and many studies relying only on self-report questionnaires, Greenfield, Subrahmanyam, & Eccles, 2012). A content analysis of coverage of all media (including television and the telephone) found that only 2.88% of articles in Developmental Psychology covered any form of media from 2003 – 2012 (Okdie et al, 2014). Although a literature on digital communication is flourishing in journals on media and communication, our understanding of what digital communication means for adolescents’ lives could be further enhanced by theories and methods from the field of psychology.…”
mentioning
confidence: 99%